Legislative oversight in Nigeria: an empirical review and assessment. Issue 1 (2nd January 2016) - Stapenhurst, Rick; Jacobs, Kerry; Olaore, Oladeji
ABSTRACT: This article builds upon and extends the analyses presented by Fashagba (2009) and drills down on the analyses of oversight in Nigeria presented by Pelizzo and Stapenhurst (2014). It presents more nuanced findings. Based on an in-country document search and 45 personal interviews with politicians, parliamentary staff, civil society representatives and journalists, the article demonstrates that the Nigerian National Assembly possesses the tools and constitutional powers to undertake oversight; what it lacks so far is the political will of National Assembly representatives and senators to use these tools and powers effectively.